Sobre a cronologia absoluta das grutas artificiais da Estremadura portuguesa - Cardoso, João Luís (2017)
A serles of radiocarbon dates from bone objects allow for a new proposal for the absolute chronology of the Upper Neolithic of the Portuguese Estremadura, the analysis of an ensemble of ornamental objects in bone from 5 different burial sites (artificial and natural caves) confirms the longevity of artifacts which registered a maximum incidence in the Upper Nealithic burial areas (dated for the first time) and survived throughout the Copper Age.